Growth Model and Tectonic Significance of the Guman Fold Along the Western Kunlun Mountain Front (Xinjiang, China) Derived From Terrace Deformation and Seismic Data - Xu, Jianhong; Chen, Jie; Arrowsmith, J. Ramón; Li, Tao; Zhang, Boxuan; Di, Ning; Pang, Wei (Frontiers in Earth Science, 2020)
The activity of blind thrust faults drives fold deformation of overlying strata, leading the folds to be geometrically related to the underlying blind thrust faults. However, it is often challenging to select an appropriate kinematic model for a thrust fault-related fold. To construct the model of the Guman fold in front of the Western Kunlun Mountains in western China, we interpret deformed terrace profiles and a high-resolution seismic reflection profile that crosses the fold. Combining deformation characteristics of the terrace profiles and subsurface structures interpreted from the seismic reflection data, the Guman fold is best explained as a fault-bend fold with lower flat-ramp-upper flat geometry that grows by kink-band migration. Previous studies and the seismic reflection profile show that the blind fault ramp dips 20±4° to the south. Using the fault bend fold model with Monte Carlo probability distributions, the uplifted and dated T1c terrace surface (250±35 ka) and fault geometry indicate a slip rate of 2.6+1.3/-0.4 mm/yr along the underlying fault ramp. The uplift of the pre-growth strata across the underlying fault ramp combined with the fold initiation in the early Pleistocene (2.14–1.8 Ma) indicate a long-term slip rate of 1.7+0.6/-0.2 mm/yr along the underlying fault ramp. For a lower flat-ramp-upper flat fault-bend fold with fault dip of 20°, 13% of the slip along the underlying fault ramp would be absorbed by the fold above the fault ramp, whereas 87% of the slip will be transferred forward along the upper fault flat. Therefore, the shortening accommodated by the Guman anticline is 0.34+0.18/-0.06 mm/yr while the slip rate along the upper fault flat is 2.3+1.1/-0.4 mm/yr since the T1c terrace abandonment. This result explains why the shortening of the Guman Anticline is largely hidden from the relative movement of GPS sites to the north and south of the fold. These findings support the view that most of the crustal shortening of the West Kunlun Mountains is transferred basinward along the shallow detachment and is likely ultimately absorbed by the Mazartagh Thrust located 200 km away in the hinterland of the Tarim Basin.